Dispersion of inflation expectations in the European Union during the global financial crisis - Jan Acedanski; Julia Wlodarczyk (Institute of Economic Research (IER), 2015)
Inflation expectations, both their median and dispersion, are of a great importance to the effectiveness of monetary policy. The goal of this paper is to examine the impact of the global financial crisis on dispersion of inflation expectations in the European Union. Using European Commission's survey data, we find that in the early phase of the crisis the dispersion dropped rapidly but then, after Lehman Brothers' collapse, the trend reversed and these fluctuations cannot be explained by movements of inflation rates and other commonly used factors. We also observe that, in the new European Union member states, the initial drop of the dispersion was weaker whereas the subsequent rise was stronger as compared to the old member states.
Keywords: C33; C42; D84; E31; 330; inflation expectations; survey data; global financial crisis; European Union